Fabrication of multi-material multi-functional 3D printed structures - Gobi, Raveen (Nanyang Technological University, 2024)
This experiment aims to fabricate multi-material polymers in a single print using Fused Granulated Fabrication (FGF) to provide a wide range of potential novel properties. With the combination of multiple materials and 3D printing, it provides more flexibility to create multi-functional structures that are essential in various applications. The FGF method was chosen to test the ability to perform in-situ blend of different polymers. By using a polymer blend, the multi-functionality and interfacial properties of the polymers were also investigated. PLA and TPU are the two polymers used for the multi-material printing due to their opposing rheological properties as well as for the ease of printing. This report entails the tests done to determine new properties and printing parameters of the multi-material polymers. Different ratios of PLA/TPU blend were prepared to test for their optimal printing parameters. The optimally printed specimens were then tested for their shear stresses at the boundary interface. The compressive properties were also obtained by varying the percentage of infills. The heating properties of TPU/cTPU blend were observed using a thermal imaging camera. To showcase the multi-functionality of the specimens, an insole is designed with the optimal PLA/TPU blend with a TPU/cTPU heating layer. Results shows that gradual change of PLA and TPU at the interface provides greater bonding. Majority PLA-based specimens exhibits higher compressive stresses due to their high rigidity. The addition of carbon black in cTPU led to different optimal printing parameters from TPU. FGF method also indicates the difference in heat conduction across TPU/cTPU samples. Further steps may be taken to test for other properties for future work.